Experiences of Mothers Who Have Children Who Are Victims of Sexual Violence - Dewi, Fitri; Khumas, Asniar; Ansar, Wilda (Polteknik Ilmu Pemasyarakatan, 2025)
Sexual violence against children has a profound psychological impact, not only on the victim but also on the parents, especially the mother. This study aims to describe the experience of mothers in caring for children who are victims of sexual violence. This study uses a qualitative method with a case study approach. The data collection technique uses in-depth interviews with three mothers whose children have experienced sexual violence and adds five people closest to the mother (significant others) who are analyzed using driven data. The results of this study indicate that mothers experience various emotional stress, namely sadness, disappointment, shock, anger, blaming themselves to wanting to end their lives. In addition, mothers face social stigma in the eyes of the community by blaming mothers for cases experienced by children. Social support from the family, UPTD PPA, plays a very important role in the role of a mother's adaptation not to blame herself for what her child experiences. The implication of this study is to provide the importance of psychosocial assistance for parents, especially mothers, and strengthening integrated services for victims of sexual violence against children.